The Role of Consumer Easy and Consumer Confidence in Forming Interest Purchase on Go-Food Services - Vidyanata, Deandra (Jurnal Entrepreneur dan Entrepreneurship, 2019)
Change and development of technology is something that cannot be denied anymore in the industrial era 4.0. This can be a challenge and an opportunity for Micro, Small and Medium Enterprises (MSME) entrepreneurs depending on how the MSMEs are responding to the development of information technology. The development of information technology is accompanied by the proliferation of various online applications to facilitate people’s lives in this digital age, one of which is the GoJek application. Go-Jek is the first digital-based motorcycle taxi application in Indonesia that offers a variety of services for its users, one of which is the delivery service available in the Go-Food service. This study aims to analyze the effect of perceived ease of use and trust on the repurchase interest in Go-Food features in the Go-Jek application. The sampling technique used in this study is purposive sampling using a Partial Least Square analysis tool with a population of all users of Go-Food services in the city of Surabaya. The results of this study are that without consumer confidence in the application provider, the convenience offered by an application is not able to cause the formation of repurchase interest. The results of this study are expected to be a theoretical basis for SMEs to encourage SMEs to take advantage of the opportunities gained from technological developments in this digital era.